Implementing a guideline for acute tonsillitis using an ambulatory medical unit. Issue 5 (10th April 2019) - Perkins, C; Ray Brown, F; Pohl, K; McLaren, O; Powles, J; Thorley, R
Abstract: Objective: Acute tonsillitis represents a significant proportion of admissions to ENT departments nationally. Given current hospital pressures, it is vital to look for safe alternatives to admission. This study explores the safe management of patients in an ambulatory medical unit, without the need for admission. Methods: A retrospective review of 48 patients' notes was carried out. Following the development and implementation of a guideline for acute tonsillitis, a prospective re-audit of 41 patients was carried out, measuring length of stay, overnight admissions and re-admissions. Results: The rate of overnight admission following implementation of the guideline fell from 0.75 to 0.29, and average length of stay dropped from 19.2 to 9.5 hours. There were two re-admissions in each cycle of the audit, which represents a non-significant increase. Conclusion: The tonsillitis guideline has significantly reduced admissions and length of stay. Re-admissions remain low, demonstrating that this is a safe and cost-effective intervention.